2002
DOI: 10.1088/0964-1726/11/2/313
|View full text |Cite
|
Sign up to set email alerts
|

Thermal post-buckling and aeroelastic behaviour of shape memory alloy reinforced plates

Abstract: A novel concept is proposed: the use of shape memory alloy (SMA) to reduce panel thermal deflection and flutter responses. SMA has a unique ability to recover large pre-strains completely when the alloy is heated above the austenite finish temperature Af. The transformation austenite start temperature As for nitinol can be anywhere between -60 °F (-50 °C) and +340 °F (+170 °C) by varying the nickel content. During the recovery process, a large tensile recovery stress occurs if the SMA is restrained. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 18 publications
1
47
0
1
Order By: Relevance
“…This behaviour is often secondary in other applications but can be very important in manipulating the dynamic response of a structure. In one study [40], it was shown that thermally-induced postbuckling deflection could be decreased by increasing the volume fraction of SMA fibres or the prestrain (detwinned strain) of the SMA. It also happened that the natural frequencies for each mode of vibration were decreased due to the added weight and reduced stiffness of the added SMA, thus changing the structural flutter response.…”
Section: Fixed-wing Aircraft and Rotorcraft Applicationsmentioning
confidence: 99%
“…This behaviour is often secondary in other applications but can be very important in manipulating the dynamic response of a structure. In one study [40], it was shown that thermally-induced postbuckling deflection could be decreased by increasing the volume fraction of SMA fibres or the prestrain (detwinned strain) of the SMA. It also happened that the natural frequencies for each mode of vibration were decreased due to the added weight and reduced stiffness of the added SMA, thus changing the structural flutter response.…”
Section: Fixed-wing Aircraft and Rotorcraft Applicationsmentioning
confidence: 99%
“…6 Several subsequent research efforts have investigated SMAHC laminates for a variety of applications. [7][8][9][10][11] The ECTE model has been used previously in a research code to analyze the static and dynamic response of beam and plate structures. 5,12,13 It is the objective of this study to demonstrate SMAHC structural analysis using the ECTE model within the framework of commercial finite element codes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several theoretical and finite element models have been proposed to evaluate the effect of SMAs fiber when the composite structures subjected to various loading conditions (Ref [13][14][15][16][17][18][19][20]. For instance, Tawfik et al (Ref 13) utilized a nonlinear finite element model to study the effectiveness of a SMA-embedded isotropic panel on the critical buckling temperature, postbuckling deflection, free vibration, and flutter boundary.…”
Section: Introductionmentioning
confidence: 99%